Guinea : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2013)
This paper presents a Joint Staff Advisory Note on Guinea's Poverty Reduction Strategy Paper (PRSP). Baseline economic growth is projected to accelerate to 5.2 percent in 2014 and beyond, up from just under 4 percent in 2012. This projection is based on an acceleration of economic growth in the construction sector in response to massive investment outlays by mining companies. Private investment is projected to increase from 17.8 percent of GDP in 2012 to more than 40 percent in 2014. The PRSP proposes a sharp increase in funding for education as a share of total public expenditures over the PRSP period, while total fiscal resources also increase.